Corporate Governance Issues in the Public Sector: Board Perspective and Peculiarities - Lartey, Peter Yao; Kong, Yusheng; Afriyie, Stephen; Santosh, Rupa Jaladi; Bah, Fatoumata Binta Maci (Brazilian Journal of Operations & Production Management, 2020)
Goal: the objective of the paper is to extend the discussions on corporate governance to the public sector and examine good governance from a Ghanaian institutional context. Design / Methodology / Approach: literature is based on relevant theoretical concepts and seven explanatory variables of corporate governance. Primary data was abstained through structured questionnaires administered to public servants from the Ministries, Departments and Agencies– MDA’s in Accra. Ordinary Least Square multiple regression was employed to analyze a total valid sample of 568. The findings represent the opinions of board of directors, internal auditors, senior management and employees. Results: the empirical result shows that audit committees, leadership, board effectiveness, accountability and directors’ qualification are strong determinants of good governance in public organizations. However, board size has no impact on good governance when board independence is negative. There is evidence that international corporate governance principles are reasonably visible without any significant deviations. Limitations of the investigation: The study is empirically limited with the absence of key variables such as corruption, ethnicity and tribal politics in public organizations in Ghana. These are major factors associated with institutional governance in developing countries. Practical Implications: the study observed a negative relationship between board independence and good governance attributed to lack of board diversity. The study implies that gender balanced boards composed of higher ratio of female directors could enhance decision-making and guarantee board effectiveness. Originality / Value: the study emphasizes that public and private organizations share almost similar governance indicators, considering the model estimation. There is evidence that corporate governance is gaining popularity in the public sector, a discussion that is often limited to the private sector. The study contributes to the limited existing findings on the subject from a Ghanaian institutional context. Finally, the results validate many empirical opinions about the negative relationship between good governance and board size from different institutional environments.